Marketing w handlu i usługach - Otto, Jacek; Olczak, Artur (Wydawnictwo Politechniki Łódzkiej, 2007)
[...] Głównym celem książki jest przedstawienie podstaw teoretycznych marketingu w handlu i usługach, uwzględniając przy tym kontekst zagadnień ogólniejszych, uniwersalistycznych, które mogą pomóc lepiej zrozumieć charakter zmian i nowych trendów w marketingu, których nie sposób pominąć. Książka składa się z czterech rozdziałów. Rozdział pierwszy ma charakter wprowadzenia do problematyki handlu i usług oraz ich roli i funkcji, jakie pełnią w nowoczesnej gospodarce. Starano się uwypuklić przede wszystkim nowe kierunki i zmiany zachodzące w obu sektorach w kontekście otoczenia międzynarodowego. W rozdziale drugim poświęcono uwagę głównie czynnikom i uwarunkowaniom, które mają istotny wpływ na wybór określonej koncepcji działań marketingowych w handlu i usługach. Zawarte tutaj rozważania dotyczą także budowania „wartościowych" relacji z klientami. Dla ich kształtowania i zarządzania nimi nieodzowne staje się wprowadzanie systemów typu CRM. Rozdział trzeci przybliża istotę koncepcji marketingu relacji oraz podstawowe instrumenty tej koncepcji, takie jak: jakość, marketing wewnętrzny, komunikacja interaktywna, programy lojalności. W ostatnim rozdziale zaprezentowano wybrane działania marketingowe stosowane w handlu. Omówione zostały przede wszystkim kluczowe elementy marketingu w handlu detalicznym, takie jak: lokalizacja, wizerunek firmy handlowej, zadania personelu sprzedaży oraz metody i techniki zarządzania merchandisingiem. Rozważania zawarte w tym rozdziale zostały uzupełnione przedstawieniem nowych form organizacji przedsiębiorstw handlowych działających w strukturach sieciowych. Publikacja jest przeznaczona głównie dla studentów uczelni ekonomicznych, szczególnie kierunków zarządzania i marketingu. Może być również przydatna osobom pracującym w sektorze handlu i usług. Autorzy wyrażają nadzieję, iż książka okaże się pożyteczną lekturą i spotka się z życzliwym przyjęciem.

Looking on marketing activities what proceed in both sectors - trade and services - We can find possible the strong relationships between them. Putting up demarcation border seems with time difficult between this what We treat as state service and this what We can definite stricte as „trade" character. Therefore also generał joining services and trade off er becomes as a common treatment. In new marketing conception called ,,relationship marketing" or "partnership marketing" whole activities are focused on complex service the and spread the long - term relations with customers, because of these links build and create both for customers the new "added value". Equally essential in trade and services marketing is initiation ,,intelligent" offer. It means innovative IT products, technology where the service is key point in providing for customers' needs and even more creating new desires. Obviously in spite new methods, tools market communication, the basie foundations, values and aims remain the same. There are creation "value added" and absolutely „new value". In book ,,Marketing in Trade and Services" We were tried to present in wider context the questions and issues the taking into account the character of changes and new trends in marketing including regard on the intemational environment. lt shows that the companies in their marketing strategies concentrate on building with customers valuable relations and other marketing issues in trade and services as well as part of whole world modem economy and management. And that why „value" and „marketing relations" with customers are still sustain the basie paradigms of marketing at all. It therefore it showed how was also the „value" be built how and the process of formation and management relations are supported informatics systems of type the CRM (Customer Relationship Management). The marketing in trade and services is oriented on direct effective range contacts with customers. That is why was emphasized issues connected know ledge of management in retail sale and marketing. First of all this w hat the state the content of marketing in this area is called „merchandising". Authors bases on own experiences and practical knowledge guess that clue elements and instruments which decide about success in market is the location, image (known brand) of firm, management of category product and assortment and profit margins place promotion and visual merchandising on the one hand are required some marketing standards for better consumer recognition their outlets. Other hand are this marketing must be strategie managed to fit for different targets groups or even individual clients.
Dla studentów uczelni ekonomicznych, szczególnie kierunków zarządzania i marketingu.
Poszczególne rozdziały opracowali: J. Otto: Wstęp; rozdz. II, III, Podsumowanie A. Olczak: rozdz. I i IV
Keywords: marketing usług; handel detaliczny; relacje z klientami; marketing relacyjny; działalność handlowa; service marketing; the retail trade; customer relations; relationship marketing; commercial activities